Genetic and evolution analysis of extrafloral nectary in cotton - Hu, Wei (Plant Biotechnol J, 2020)
Extrafloral nectaries are a defence trait that plays important roles in plant–animal interactions. Gossypium species are characterized by cellular grooves in leaf midribs that secret large amounts of nectar. Here, with a panel of 215 G. arboreum accessions, we compared extrafloral nectaries to nectariless accessions to identify a region of Chr12 that showed strong differentiation and overlapped with signals from GWAS of nectaries. Fine mapping of an F(2) population identified GaNEC1, encoding a PB1 domain‐containing protein, as a positive regulator of nectary formation. An InDel, encoding a five amino acid deletion, together with a nonsynonymous substitution, was predicted to cause 3D structural changes in GaNEC1 protein that could confer the nectariless phenotype. mRNA‐Seq analysis showed that JA‐related genes are up‐regulated and cell wall‐related genes are down‐regulated in the nectary. Silencing of GaNEC1 led to a smaller size of foliar nectary phenotype. Metabolomics analysis identified more than 400 metabolites in nectar, including expected saccharides and amino acids. The identification of GaNEC1 helps establish the network regulating nectary formation and nectar secretion, and has implications for understanding the production of secondary metabolites in nectar. Our results will deepen our understanding of plant–mutualism co‐evolution and interactions, and will enable utilization of a plant defence trait in cotton breeding efforts.